Reevaluation of Criteria and Establishment of Models for Total Thyroidectomy in Differentiated Thyroid Cancer - Wu, Zhenghao; Xiao, Yunxiao; Ming, Jie; Xiong, Yiquan; Wang, Shuntao; Ruan, Shengnan; Huang, Tao (Frontiers in Oncology, 2021)
Introduction: After the publication of the 2015 ATA guidelines, the indication for total thyroidectomy (TT) was reported to be underestimated before surgery, which may lead to a substantial rate of secondary completion thyroidectomy (CTx). Methods and materials: We retrospectively analyzed differentiated thyroid cancer patients from Wuhan Union Hospital (WHUH). Univariate analysis was performed to evaluate all preoperative and intraoperative factors. New models were picked out by comminating and arranging all significant factors and were compared with ATA and NCCN guidelines in the multi-center prospective DTCC cohort. Results: 5331 patients from WHUH were included. Preoperative and intraoperative criteria individually identified 906 (17.0%) and 213 (4.0%) patients eligible for TT. Among all factors, age < 35 years old, clinical N1, and ultrasound reported local invasion had high positive predictive value to predict patients who should undergo the TT. Accordingly, we established two new models which minorly revised ATA guidelines but performed much better. Model 1 replaced ‘nodule size > 4cm’ with ‘age < 35 years old’, and achieved significant increase in the sensitivity (WHUH: 0.711 vs. 0.484; DTCC: 0.675 vs. 0.351). Model 2 simultaneously demands the presence of ‘nodule size > 4cm’ and ‘age < 35 years old’, which had a significant increase in the specificity (WHUH: 0.905 vs. 0.818; DTCC: 0.729 vs. 0.643). Conclusion: All high-risk factors had limited predictive ability. Our model added young age as a new criterion for total thyroidectomy to get a higher diagnostic value than guidelines.